Leadership development in health information management (HIM): literature review. Issue 4 (26th September 2019) - Low, Sarah; Butler-Henderson, Kerryn; Nash, Rosie; Abrams, Kelly
Abstract : Purpose: The health information management (HIM) profession lacks clarity around leadership and leadership development. To date, little empirical research exists on this topic, and it is unclear if broader approaches for healthcare leadership are suitable. This paper aims to explore which the leadership styles are relevant to the HIM profession. The findings were also used to inform a discussion on how HIM professionals could develop these leadership styles. Design/methodology/approach: Through a systematic scoping literature review, deductive thematic analysis was undertaken to extrapolate common themes around this style of leadership based on transversal competency domains that reflect twenty-first century skills (i.e. critical thinking and innovation, interpersonal, intrapersonal and global citizenship) (Bernard, Watch and Ryan, 2016; UNESCO, 2015 ). This approach enabled the findings to be discussed from a leadership development perspective. Findings: Analysis of the literature revealed that a relational leadership style through a team-based approach is required. Literature studies on how to develop leadership competencies were not found. Research limitations/implications: Future policy and research implications include the need for research on transversal competencies to determine if they can shape HIM leadership development. Practical implications: This leadership style and competencies proposed are relevant across many occupations and may have broader applications for leadership research, education and development. Originality/value: This paper defines the style of leadership required in the HIM profession and identifies a succinct set of contemporary competencies to inform the development of this type of leadership.